Personal digital bodyguards for e-security, e-learning and e-health: A prospective survey - Plamondon, Réjean; Pirlo, Giuseppe; Anquetil, Éric; Rémi, Céline; Teulings, Hans-Leo; Nakagawa, Masaki (Pattern recognition, 2018)
•A prospective survey that merges the e-security, e-health and e-learning on mobile devices.•A vision of the future developments in on-line processing of handwriting.•A new mobile device application, the Personal Digital Bodyguard.•An integrated view of one possible outcome of research in human motor control.•A common goal for computer scientists, hardware engineers, neuroscientists, education experts. The widespread availability of hand-held devices like tablets, phablets and smart phones, along with their new handwriting digitizing and their increased computing powers, enable these to process the graphomotor dimension and the lognormal trends of human handwriting. By exploiting such capacity, it becomes possible to extend these mobile devices into Personal Digital Bodyguards (PDBs). PDBs will be able to supplement people's sensitive data protection with signature verification, equipment use security with writer authentication and handwritten CAPTCHAs processing (e-security), and to enhance human-machine interaction performances through words spotting and handwriting recognition (e-recognition). For young children, these tools will turn into interactive toys helping them to learn and master their fine motor control and become better writers. For advanced students they will enable sophisticated systems for (e-learning) and (e-testing). Moreover, PDBs will also be able to provide the user with fine motor control monitoring, which can detect stress, aging and health problems (e-health). This paper presents a prospective survey of various projects dealing with these five e-fields of investigation, focussing on state of the art results and providing directions in research and development, under the theoretical umbrella of the Kinematic Theory of human movements and its Lognormality Principle. From a practical point of view, the concept of lognormality provides a fundamental common thread, an integrative psychophysical standpoint to track the graphomotor problems of signature verification, writer identification, handwriting generation, recognition and learning.